The use of ensiled olive cake in the diets of Friesian cows increases beneficial fatty acids in milk and Halloumi cheese and alters the expression of SREBF1 in adipose tissue - Neofytou, M. C.; Miltiadou, Despoina; Sfakianaki, Eleftheria; Constantinou, Crystle; Symeou, Simoni; Sparaggis, Dionysis; Hager-Theodorides, Ariadne Loukia; Tzamaloukas, Ouranios (My University, 2020)
This study aimed to evaluate the effect of dietary inclusion of ensiled olive cake, a by-product of olive oil production, on milk yield and composition and on fatty acid (FA) profile of milk and Halloumi cheese from cows. Furthermore, the effect of olive cake on the expression of selected genes involved in mammary and adipose lipid metabolism was assessed in a subset of animals. A total of 24 dairy cows in mid lactation were allocated into 2 isonitrogenous and isoenergetic feeding treatments, named the control (CON) diet and the olive cake (OC) diet, in which part of the forages (alfalfa, barley hay, and barley straw) were replaced with ensiled OC as 10% of dry matter according to a 2 × 2 crossover design with two 28-d experimental periods. At the end of the second experimental period, mammary and perirenal adipose tissue samples were collected from 3 animals per group for gene expression analysis by quantitative reverse-transcription PCR. The expression of 11 genes, involved in FA synthesis (ACACA, FASN, G6PDH), FA uptake or translocation (VLDLR, LPL, SLC2A1, CD36, FABP3), FA saturation (SCD1), and transcriptional regulation (SREBF1, PPARG), was evaluated. No significant differences were observed between groups concerning milk yield, fat percentage, protein percentage, and protein yield (kg/d), whereas milk fat yield (kg/d) increased in the OC group. Dietary supplementation with ensiled OC modified the FA profile of milk and Halloumi cheese produced. There was a significant decrease in the concentration of de novo synthesized FA, saturated FA, and the atherogenic index, whereas long-chain and monounsaturated FA concentration was increased in both milk and cheese. Among individual saturated FA, only stearic acid was elevated, whereas among individual monounsaturated FA, increments of oleic acid (C18:1 cis-9) and the sum of C18:1 trans-10 and trans-11 acids were demonstrated in milk and Halloumi cheese produced. Although no diet effect was reported on total polyunsaturated FA, the concentration of CLA cis-9,trans-11 was increased in both milk and Halloumi cheese fat of the OC group. The expression of the genes tested was unaffected apart from an observed upregulation of SREBF1 mRNA expression in perirenal fat from cows fed the OC diet. Milk FA differences observed were not associated with alterations in mammary expression of genes involved in FA synthesis, uptake, translocation, and regulation of lipogenesis. Overall, the inclusion of ensiled OC in cow diets for a 4-wk period improved, beneficially for human health, the lipid profile of bovine milk and Halloumi cheese produced without adversely affecting milk yield and composition or the expression of genes involved in lipid metabolism of mammary and adipose tissues in cows.
Keywords: Ensiled olive cake; Milk fatty acid; Halloumi cheese; Gene expression